Sexual Orientation, Human Rights, and Corporate Sponsorship of the Sochi Olympic Games: Rethinking the Voluntary Approach to Corporate Social Responsibility. Issue 78 (28th February 2014) - Van Detta, Jeffrey A.
Multi-national enterprises (MNEs) have provided substantial sponsorship for the Sochi Winter Olympic Games despite a host-country government that has recently enacted stunningly harsh legislation aimed at the Lesbian, Gay, Bisexual, Transgender, and Intersex (LGBTI) communities within Russia. This is a Corporate Social Responsibility (CSR) problem. Should Europe address it through voluntary corporate compliance, Europe's historically preferred mode of promoting CSR? Or should Europe reconsider whether it can more effectively promote CSR compliance legislatively – and if so, by what kind of legislation? To honor the explicit and increased protections of human rights against sexual orientation discrimination in the Treaty of Amsterdam and the Charter of Fundamental Human Rights, more than voluntary, good intentions are needed. Particularly since the United States has effectively bowed out of enforcing CSR through the American federal courts, there now exists a regulatory lacuna that the European Commission is best situated to fill through the precision offered by judicious rulemaking. The article ultimately proposes an approach that combines the public-pressure engine that fuels voluntary CSR with public disclosures mandated by law to optimize the information and mobilization of public opinion and pressure – factors particularly noteworthy given the powerful "branding" benefits that MNEs seek through Olympic sponsorship.